Kedudukan Filsafat Keilmuan Dalam Penerapan Hukum Islam - Jailuddin, Syuaib; M, Marilang; Siola, Nasir (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This paper discusses the meaning, concept, position, and role of philosophy in Islam which is divided into two main views: the group that rejects philosophy and the group that accepts it. The group that rejects philosophy views it as a threat to the purity of Islamic teachings, while the group that accepts philosophy sees it as a tool to deepen the understanding of Islamic teachings through the use of reason and rationality. Philosophy has an important position in Islam, as evidenced by the history of Muslim philosophers such as Al-Farabi, Ibn Sina, and Ibn Rushd, who not only developed Islamic thought but also bridged the traditions of Greek and Western philosophy. In the context of Islam, philosophy helps answer contemporary challenges, understand the wisdom of religious teachings, and encourage a critical and rational approach to sacred texts. The philosophical approach in Islam also has a significant impact on the formation of science, such as ushul fiqh and tasawuf, and provides a framework for thinking to face modern challenges. Thus, philosophy and Islam complement each other in forming a deep and relevant understanding of religious teachings in everyday life.